Institutional change and the implementation of innovative management accounting frameworks in a Portuguese government agency - Pimentel, Luís Pedro Vilela (2015)
This thesis relates to an investigation concerning institutional change that occurred in a Portuguese government agency, Instituto de Gestão Financeira da Segurança Social - IGFSS (Social Security Financial Management Institute). Concretely, innovative management accounting and control frameworks were implemented. Taking into account pressures and trends that came from the upper field levels of the organization – the economic and political level and the organizational field level (Dillard et al., 2004), the investigation analyses the way how IGFSS reacted to those pressures and trends, exploring the internal dynamics of change that were visualized in the organization. Borrowing mainly from the contributions of Cruz et al. (2009), Cruz et al. (2011), and Lounsbury (2001, 2008), those internal dynamics were translated into practice variation. Furthermore, the research analyses the way the organization implemented divergent change, facing the previous public administration mode that was being used in IGFSS. Drawing on the model of the process of institutional entrepreneurship (Battilana et al., 2009), the way the process was rooted with the support of collective action is analyzed. A refined model is proposed, by highlighting the relevance of factors such as actors’ organizational and structural capabilities, communication, cooperation, or motivation. The new management model and the link between the several innovative frameworks, particularly the integration of total quality management and a balanced scorecard, are also depicted. Explanatory, illustrative and descriptive studies supported the case study that was conducted (Ryan et al., 2002; Scapens, 1990; see also Keating, 1995; Vaivio, 2007).